Latvijas studentu uzņēmējkompetenču novērtējums - Tamisārs, Mārtiņš (Latvijas Universitāte, 2016)
Bakalaura darbs „Latvijas studentu uzņēmējkompetenču novērtējums” izstrādāts ar mērķi novērtēt Latvijas studentiem raksturīgās uzņēmējkompetences, kā arī noteikt studentus ietekmējošos uzņēmējdarbības vides faktorus, izvirzīt priekšlikumus studentu uzņēmējkompetenču veicināšanai un uzņēmējdarbības atbalsta infrastruktūras uzlabošanai Latvijā. Bakalaura darbs sastāv no trīs daļām. Pirmajā daļā tiek veikts vispārējs uzņēmējdarbības jēdziena un uzņēmējkompetenču teorētiskais apskats. Otrajā daļā autors analizē studentus ietekmējošos uzņēmējdarbības vides faktorus Eiropas Savienībā un Latvijā, uzsvaru liekot uz uzņēmējdarbības atbalsta infrastruktūru. Trešajā daļā tiek veikts Latvijas studentu uzņēmējkompetenču novērtējums un ekspertintervijas. Darba rezultātā secināts, ka studenti, kam piemīt augstāks uzņēmējkompetenču novērtējums, biežāk apmeklē uzņēmējdarbības atbalsta institūcijas un pasākumus.

In the bachelor’s thesis „The evaluation of students’ entrepreneurial competencies in Latvia” a research has been carried out to evaluate the entrepreneurial competencies of Latvian students, determine the factors affecting entrepreneurial environment of the students and propose possible solutions in order to develop students’ entrepreneurial competencies and improve the students’ entrepreneurship support infrastructure in Latvia. The bachelor thesis consists of three parts. In the first part a comprehensive theoretical overview of entrepreneurship and entrepreneurial competencies has been done. In the second part the author has analyzed entrepreneurial environment factors that affect students emphasizing the business support infrastructure. In the third part of bachelor thesis a research has been carried out to evaluate the students’ entrepreneurial competencies and the expert surveys have been conducted.
Evaluation of students' entrepreneurial competencies in Latvia
Keywords: Ekonomika; uzņēmējkompetences; uzņēmējdarbība; entrepreneurial competencies; entrepreneurship